2021
DOI: 10.1080/03007995.2021.1947218
|View full text |Cite
|
Sign up to set email alerts
|

A medicine adoption model for assessing the expected effects of additional real-world evidence (RWE) at product launch

Abstract: Introduction:The optimal launch and adoption of novel medicines require effective navigation of the commercial and regulatory landscape, including three key gatekeeper groups: regulators, payors, and prescribers. Traditionally, despite lacking generalisability, the pharmaceutical industry provides Phase III randomized controlled trial evidence to gatekeepers. Despite additional real-world evidence (RWE) improving the generalisability of evidence, the provision of RWE remains in its infancy. The industry may us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…MAPPs play a critical role in guaranteeing that key messages are informed by sound scientific evidence and no disingenuous assertions are made [ 32 ], which explains their high level of accountability for pharmaceutical company activities. MAPPs also design and implement RWE to answer questions unanswered by registered clinical trials [ 33 , 34 ], therefore their value is not only in their ability to influence successful medicine adoption but to do so in many different ways. Thus, the findings of this study suggested that MAPPs were of key value to pharmaceutical company success and they were the only internal stakeholder of those studied able to deliver this value.…”
Section: Discussionmentioning
confidence: 99%
“…MAPPs play a critical role in guaranteeing that key messages are informed by sound scientific evidence and no disingenuous assertions are made [ 32 ], which explains their high level of accountability for pharmaceutical company activities. MAPPs also design and implement RWE to answer questions unanswered by registered clinical trials [ 33 , 34 ], therefore their value is not only in their ability to influence successful medicine adoption but to do so in many different ways. Thus, the findings of this study suggested that MAPPs were of key value to pharmaceutical company success and they were the only internal stakeholder of those studied able to deliver this value.…”
Section: Discussionmentioning
confidence: 99%
“…Accurate construct measurement in social sciences can be argued as being just as important as in natural sciences. However, given the key decisions made on the basis of findings from clinical studies particularly in the context of the adoption of new medicines [ 11 ] the consequences of inaccurate findings in this setting can be particularly harmful to the very patients the investigators are seeking to support.…”
Section: Discussionmentioning
confidence: 99%
“…Each subsystem requires specific evidence to satisfy its internal logic for that medicine to progress in its adoption. Evidence of quality of life improvements in rare disease patients receiving a particular treatment is valuable in payor discussions [ 10 ] and therefore an essential input for the Payor subsystem [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accurate construct measurement in social sciences can be argued as being just as important as in natural sciences. However, given the key decisions made on the basis of ndings from clinical studies particularly in the context of the adoption of new medicines [11] the consequences of inaccurate ndings in this setting can be particularly harmful to the very patients the investigators are seeking to support.…”
Section: Discussionmentioning
confidence: 99%
“…Each subsystem requires speci c evidence to satisfy its internal logic for that medicine to progress in its adoption. Evidence of quality of life improvements in rare disease patients receiving a particular treatment is valuable in payor discussions [10] and therefore an essential input for the Payor subsystem [11].…”
Section: Introductionmentioning
confidence: 99%